Adaptação transcultural das avaliações “SOSI-M Structured Observation Sensory Integration - Motor” e “COP-R Comprehensive Observations of Proprioception - revised” e estudo do desempenho populacional preliminar de crianças e adolescente brasileiros - Ovando, Laura Maria Koopman (2024)
Introduction: Assessment plays a fundamental role in the development of therapeutic planning and intervention strategies. However, there is a paucity of validated instruments for identifying sensory processing disorders within the Brazilian population. The SOSI-M (Structured Observation of Sensory Integration – Motor) and the COP-R (Comprehensive Observations of Proprioception – Revised) are standardized tools that quantitatively assess motor components related to sensory processing, offering a rapid and cost-effective application method grounded in Ayres’ clinical observations. These instruments evaluate, through direct observation of performance, proprioceptive and vestibular processing, motor planning, and postural control abilities in children aged 5 to 14 years. The SOSI-M provides psychometric data for sensory processing analysis and is administered in conjunction with the COP-R. Since these instruments were originally developed in a different cultural context, their application in Brazil necessitates a rigorous cross-cultural adaptation process. Objective: To conduct the cross-cultural adaptation and preliminary investigation of the reliability and performance of Brazilian children in the SOSI-M and COP-R assessments. Methodology: This study employs a methodological, cross-sectional, and quantitative research design, structured in three distinct stages: Stage 1 – Cross-Cultural Adaptation, Stage 2 – Pre-test and Preliminary Population Study, and Stage 3 – Validation Evidence Study. The cross-cultural adaptation (Stage 1) followed a five-step process: translation, synthesis, back-translation, expert committee review, and pre-testing. Stage 2 involved a pre-test and a preliminary assessment of the performance of a sample of Brazilian children, encompassing all five regions of the country to ensure a representative inclusion of diverse cultural and social contexts. In Stage 3, a psychometric investigation was conducted to establish validity evidence, with reliability analyzed through stability (test-retest), inter-rater equivalence, and internal consistency via Cronbach’s alpha. Results and Discussion: The cross-cultural adaptation process demonstrated methodological robustness, with all 475 items achieving an approval rate exceeding 80%, as well as endorsement from the original instrument developers. The pre-test results revealed sociocultural variations, underscoring the necessity of broader nationwide testing. Reliability analysis of the SOSI-M yielded a Cronbach’s alpha of 0.73, closely aligning with the original instrument (0.76). Inter-rater reliability indicated an excellent level of agreement (ICC = 0.996; 95% CI = 0.995–0.998, F(57, 1083) = 293.958, p < 0.001), while test-retest reliability also demonstrated high concordance (ICC = 0.992; 95% CI = 0.989–0.995, F(56, 1064) = 132.257, p < 0.001). These findings underscore the importance of further large-scale validation studies to substantiate potential sociocultural influences and enhance the robustness of validity evidence.